Temporal Dynamics of Rhizosphere Communities Across the Life Cycle of Panax notoginseng - Wei, Guangfei; Li, Mengzhi; Zhang, Guozhuang; Chen, Zhongjian; Wei, Fugang; Jiao, Shuo; Qian, Jun; Wang, Yong; Wei, Jianhe; Wang, Yitao; Meng, Xiangxiao; Fitzgerald, Martin; et al. (Frontiers in Microbiology, 2022)
Rhizosphere microbiome promotes plant growth; however, the succession of rhizosphere microbial community during the growth stages of perennial medicinal plant Panax notoginseng (P. notoginseng) is still unclear. Here, amplicon sequencing was performed to assess the succession characteristics of rhizosphere microbiomes during developmental stages. Results showed that bacterial and fungal communities were mainly shaped by the development stages. The microbial α-diversities first increased and then decreased with plant growth and the variation in microbial composition was active at the 3-year root growth (3YR) stage. The variation trend of cross-domain co-occurrence network complexity was similar to that of α-diversities. Cross-domain nodes decreased at the 3YR stage and fungal nodes increased at the 3YR stage. This study provided a detailed and systematic survey of rhizosphere microbiomes during the growth stages of P. notoginseng. The findings revealed that the development stages of P. notoginseng drove the temporal dynamics of rhizosphere communities. This study helps in harnessing the power of microbiomes to evaluate herbal medicine growth and provides valuable information to guide the microbial breeding of medical plants.